A Regional Model for the Portuguese Economy Based on a Regional Accounting Matrix - Pedro N. Ramos (European Regional Science Association (ERSA), 2001)
This paper presents a model for the Portuguese economy based on a so-called “Regional Accounting Matrix” (RAM). The RAM is an accounting table made up of information provided by the standard Portuguese National and Regional Accounts, with a similar framework than the well-known social accounting matrixes. The RAM includes regionalised information concerning the generation and the use of the households' income, but other parts of the table, namely those referring the structure of inputs in the production process, are at national level. Starting with the RAM, the paper then develops an input-output-type model closed with respect to the households' consumption. This model is based in a “no regional preference hypothesis in supplying each region”. By this hypothesis we mean that every increase in demand, even when regionally located, is complied by a national supply (and also by international imports), and not preferentially by an increase in output of the very concerned region. The model proposed for the Portuguese economy, for the year of 1995, includes the computation of several multipliers – the most striking of them describe the inter-regional income distribution process. In fact, an increase in income, at the beginning in benefit of the households living in one region, may cross the region borders and propagate into other regions, increasing then the households' income in the latter regions. The model also provides other outstanding multipliers, as those describing the effect on the regional households' income of changes in demand of 49 kinds of products, and those computing the change in output of these 49 products induced by exogenous shocks in the regional income.
Keywords: 330